Lifetime economic burden of prostate cancer - Stokes Michael E; Ishak Jack; Proskorovsky Irina; Black Libby K; Huang Yijian (BMC, 2011)
Abstract Background Prostate cancer (PCa) is the most common cancer affecting men in the United States. The initial treatment and subsequent monitoring of PCa patients places a large burden on U.S. health care systems. The objectives of this study were to estimate the total and disease-related per-patient lifetime costs using a phase-based model of cancer care for PCa patients enrolled in Medicare. Methods A model was developed to estimate life-time costs for patients diagnosed with PCa. Patients ≥ 65 years old and diagnosed with PCa between calendar years 1991-2002 were selected from the SEER database. Using SEER, we estimated survival times for PCa patients from diagnosis until death. The period of time patients contributed to treatment phases was determined using an algorithm designed to model the natural history of PCa. Costs were obtained from the US SEER-Medicare database and estimated during specific phases of care. Cost estimates were then combined with survival data to yield total and PCa-related life-time costs. Results Overall, the model estimated life-time costs of $110,520 (95% CI 110,324-110,739) per patient. PCa-related costs made up approximately 31% of total costs ($34,432). Conclusions Prostate cancer places a significant burden on U.S. health-care systems with average life-time PCa-related costs in excess of $30,000.